The CAR-HEMATOTOX risk-stratifies patients for severe infections and disease progression after CD19 CAR-T in R/R LBCL. - Rejeski, Kai; Perez, Ariel; Iacoboni, Gloria; Penack, Olaf; Bucklein, Veit; Jentzsch, Liv; Mougiakakos, Dimitrios; Johnson, Grace; Arciola, Brian; Carpio, Cecilia; Blumenberg, Viktoria; Hoster, Eva; et al. (Journal for ImmunoTherapy of Cancer, 2022)
BACKGROUND: CD19-directed chimeric antigen receptor T-cell therapy (CAR-T) represents a promising treatment modality for an increasing number of B-cell malignancies. However, prolonged cytopenias and infections substantially contribute to the toxicity burden of CAR-T. The recently developed CAR-HEMATOTOX (HT) score-composed of five pre-lymphodepletion variables (eg, absolute neutrophil count, platelet count, hemoglobin, C-reactive protein, ferritin)-enables risk stratification of hematological toxicity. METHODS: In this multicenter retrospective analysis, we characterized early infection events (days 0-90) and clinical outcomes in 248 patients receiving standard-of-care CD19 CAR-T for relapsed/refractory large B-cell lymphoma. This included a derivation cohort (cohort A, 179 patients) and a second independent validation cohort (cohort B, 69 patients). Cumulative incidence curves were calculated for all-grade, grade ≥3, and specific infection subtypes. Clinical outcomes were studied via Kaplan-Meier estimates. RESULTS: In a multivariate analysis adjusted for other baseline features, the HT score identified patients at high risk for severe infections (adjusted HR 6.4, 95% CI 3.1 to 13.1). HThigh patients more frequently developed severe infections (40% vs 8%, p<0.0001)-particularly severe bacterial infections (27% vs 0.9%, p<0.0001). Additionally, multivariate analysis of post-CAR-T factors revealed that infection risk was increased by prolonged neutropenia (≥14 days) and corticosteroid use (≥9 days), and decreased with fluoroquinolone prophylaxis. Antibacterial prophylaxis significantly reduced the likelihood of severe bacterial infections in HThigh (16% vs 46%, p<0.001), but not HTlow patients (0% vs 2%, p=n.s.). Collectively, HThigh patients experienced worse median progression-free (3.4 vs 12.6 months) and overall survival (9.1 months vs not-reached), and were hospitalized longer (median 20 vs 16 days). Severe infections represented the most common cause of non-relapse mortality after CAR-T and were associated with poor survival outcomes. A trend toward increased non-relapse mortality in HThigh patients was observed (8.0% vs 3.7%, p=0.09). CONCLUSIONS: These data demonstrate the utility of the HT score to risk-stratify patients for infectious complications and poor survival outcomes prior to CD19 CAR-T. High-risk patients likely benefit from anti-infective prophylaxis and should be closely monitored for potential infections and relapse.
EVALuna2:503898